Polyimide polymer as well as preparation method and application thereof
By introducing aromatic dibenzene methylene fluorene-type structure into the diamine structure of polyimide microporous foam material and regulating the diamine ratio, the problems of high shrinkage, poor mechanical properties and poor high temperature insulation effect are solved. It has achieved low shrinkage, high temperature resistance and excellent thermal insulation performance, which has improved its application prospects in aerospace and other fields.
Patent Information
- Application Number
- CN202311047615.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-18
- Publication Date
- 2025-02-21
AI Technical Summary
The existing polyimide microporous foam materials have problems such as high shrinkage, poor mechanical properties, and poor high temperature insulation, which affects its application and promotion in aerospace, sewage treatment and other fields.
By introducing aromatic dibenzene methylene fluorene type structure into the diamine structure, the structural rigidity of the polymer is improved, and by regulating different diamine ratios, a moderately rigid polymer chain structure is obtained, thereby reducing polyimide micropores The shrinkage rate of foam.
The low shrinkage, high temperature resistance and excellent high temperature insulation properties of polyimide microporous foam are achieved, which improves its mechanical properties and application prospects.
Smart Images

Figure CN119490655A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a class of polyimide polymers and a preparation method and application thereof, belonging to the field of material technology. Background Art
[0002] Polyimide microporous foam material is a kind of polymer material with imide structure and nanopores, and is a functional material in engineering plastics. It has high porosity, high specific surface area, low thermal conductivity and excellent dimensional stability. At the same time, it has the characteristics of high and low temperature resistance, radiation resistance, separation and adsorption, etc., so it has a wide range of applications in aerospace, sewage treatment, space exploration and other fields, and has a very broad development prospect.
[0003] At present, polyimide microporous foam materials are mainly prepared by polycondensation of dianhydride and diamine. However, the polyimide microporous foam materials obtained based on the existing two monomer structures have problems such as high shrinkage, poor mechanical properties, and poor high-temperature thermal insulation effect, which affect the application and promotion. Therefore, reducing the shrinkage of polyimide microporous foam materials through reasonable monomer structure design and improving mechanical properties and high-temperature thermal insulation properties have become important research directions. Summary of the invention
[0004] The purpose of the present invention is to provide a novel polyimide microporous foam material with low shrinkage, high temperature resistance and good heat insulation performance and a preparation method thereof, that is, by introducing an aromatic diphenylmethylene fluorene structure into a diamine structure, the structural rigidity of the polymer is improved, and by adjusting different diamine ratios, a polymer chain structure with moderate rigidity is obtained, thereby reducing the shrinkage rate of the polyimide microporous foam.
[0005] According to the first aspect of the present application, a type of polyimide polymer is provided, wherein the polyimide polymer has a structure shown in Formula I:
[0006]
[0007] Wherein, n is 10 to 100;
[0008] In Formula I, R4 is selected from one of the compounds represented by Formula I-1 and Formula I-2;
[0009]
[0010] R1 is selected from one of the structures shown in A-1 to A-10;
[0011]
[0012] R2 is selected from one of the structures shown in B-1 to B-13;
[0013]
[0014] R3 is selected from one of the structures shown in Formula I-3, Formula I-4, Formula I-5, and Formula I-6;
[0015]
[0016] Optionally, the polyimide polymer has a structure shown in Formula IV-1 or Formula IV-2:
[0017]
[0018]
[0019] In the formula IV-1 or IV-2, R1 is selected from any one of the A-type groups; wherein the A-type group is a dianhydride structure, and its structural formula is one of the structures shown in A-1 to A-10;
[0020] The R2 is selected from any one of the following B-type groups; the B-type group is a diamine structure, and its structural formula is one of the structures shown in B-1 to B-13;
[0021] The R3 is selected from any one of the following C-type groups; the C-type group is a polyaromatic amine structure, and its structural formula is one of the structures shown in Formula I-3, Formula I-4, Formula I-5, and Formula I-6.
[0022] According to a second aspect of the present application, a method for preparing the polyimide polymer described above is provided, comprising the following steps:
[0023] Reacting a mixture containing a compound represented by Formula II, a dianhydride compound, a compound represented by Formula III, and a solvent to obtain a polyimide polymer represented by Formula I;
[0024]
[0025] Wherein, the compound represented by formula II is selected from one of the structures represented by formula II-1 and formula II-2; the compound represented by formula III is selected from one of the structures represented by formula III-1, formula III-2, formula III-3, and formula III-4;
[0026]
[0027]
[0028] Optionally, the dianhydride compound is selected from at least one of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 1,4-bis(trifluoromethyl)-2,3,5,6-pyromellitic dianhydride, 4,4'-oxydiphthalic anhydride, 4,4'-thiodiphthalic anhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 4,4'-(hexafluoroisopropylene)diphthalic anhydride, 3,3,4,4-diphenylsulfonetetracarboxylic dianhydride and 4,4'-(4,4'-isopropyldiphenoxy)bis(phthalic anhydride).
[0029] Optionally, the molar ratio of the compound represented by formula II, the dianhydride compound and the compound represented by formula III is: 0.90-0.99: 1.01-1.10: 0.01-0.05.
[0030] Optionally, the molar volume ratio of the compound represented by formula II to the solvent is 3.75-7.50 mmol: 20-50 mL.
[0031] Optionally, the solvent is selected from at least one of N,N-dimethylformamide, N,N-diethylacetamide, dimethyl sulfoxide, tetrahydrofuran, and 1,4-dioxane.
[0032] Optionally, the solvent is N-methylpyrrolidone.
[0033] Optionally, the reaction temperature is 10°C to 180°C, and the reaction time is 2 to 24 hours.
[0034] Optionally, the reaction temperature is selected from any value of 10°C, 20°C, 30°C, 50°C, 80°C, 100°C, 120°C, 150°C, 180°C or a range between any two of the above values.
[0035] Optionally, the reaction time is selected from any value among 2h, 4h, 8h, 12h, 16h, 20h, 24h or a range between any two of the above.
[0036] Optionally, the reaction temperature is 20°C to 30°C, and the reaction time is 8 to 12 hours.
[0037] Optionally, the method for preparing the polyimide polymer comprises the following steps:
[0038] A mixture containing dianhydride, any one of the diamine compounds shown in formula II, and / or any one of the diamines, and a solvent is subjected to a condensation reaction, followed by a cross-linking reaction with any one of the polyarylamines of claim 1, and then subjected to gel aging, solvent replacement and supercritical drying to obtain a polyimide polymer shown in formula I.
[0039] Optionally, the molar ratio of the dianhydride to the total diamines is 1.10:1 to 1.01:1.
[0040] Optionally, the molar ratio of the dianhydride to the total diamines is selected from any value of 1.10:1, 1.05:1, 1.03:1, 1.02:1, 1.01:1, or a range between any two of the above points.
[0041] Optionally, the solvent in the solvent replacement is acetone or ethanol. Preferably, the solvent is acetone.
[0042] In the present application, the aromatic diamine compound has one of the structures shown in Formula II-1 and Formula II-2;
[0043]
[0044] The preparation method of the aromatic diamine compound comprises the following steps:
[0045] (1) subjecting a mixture I containing a benzophenone compound and a fluorene compound to an aldol condensation reaction to obtain an intermediate compound I;
[0046] (2) subjecting a mixture II containing the intermediate compound I, p-aminophenylborate hydrochloride, an alkaline solution, and a catalyst to a Suzuki coupling reaction to obtain an aromatic diamine compound represented by formula II.
[0047] Optionally, the intermediate compound III is selected from one of formula III-1 and formula III-2;
[0048]
[0049]
[0050] Optionally, when the aromatic diamine compound is a compound represented by formula II-1, the benzophenone compound is benzophenone, and the fluorene compound is 2,7-dibromofluorene.
[0051] Optionally, when the aromatic diamine compound is a compound represented by formula II-2, the benzophenone compound is 4,4'-dibromobenzophenone, and the fluorene compound is fluorene.
[0052] Optionally, the catalyst comprises tetrakis(triphenylphosphine)palladium and a phase transfer catalyst.
[0053] Optionally, the phase transfer catalyst is selected from tetrabutylammonium bromide and / or methyltrioctylammonium chloride.
[0054] Optionally, the alkaline solution is selected from potassium carbonate solution and / or potassium triphosphate solution.
[0055] Optionally, the phase transfer catalyst is methyltrioctylammonium chloride.
[0056] Optionally, the alkaline solution is selected from potassium carbonate solution.
[0057] Optionally, the molar ratio of the benzophenone compound to the fluorene compound is 4:1 to 2:1.
[0058] Optionally, the molar ratio of the benzophenone compound to the fluorene compound is selected from any value of 4:1, 3.5:1, 3.0:1, 2.5:1, 2:1 or a range between any two of the above points.
[0059] Optionally, the molar ratio of the intermediate compound I to the p-aminophenylborate hydrochloride is 1:2.1 to 1:3.3.
[0060] Optionally, the molar ratio of the intermediate compound I to the p-aminophenylborate hydrochloride is selected from any value of 1:2.1, 1:2.4, 1:2.6, 1:2.8, 1:3.0, 1:3.1, 1:3.3 or a range between any two of the above points.
[0061] Optionally, the molar ratio of the intermediate compound I to the catalyst is 1:0.05 to 1:0.3.
[0062] Optionally, the molar ratio of the intermediate compound I to the catalyst is selected from any value of 1:0.05, 1:0.1, 1:0.2, 1:0.3 or a range value between any two of the above points.
[0063] Optionally, the molar ratio of the intermediate compound I to the alkaline solution is 1:5 to 1:20.
[0064] Optionally, the molar ratio of the intermediate compound I to the alkaline solution is selected from any value of 1:5, 1:6, 1:7, 1:8, 1:10, 1:15, 1:20 or a range between any two of the above points.
[0065] Optionally, the concentration of the alkaline solution is 2.0-3.0M.
[0066] Optionally, the concentration of the alkaline solution is selected from any value among 2.0M, 2.2M, 2.5M, 2.7M, 3.0M or a range between any two of the above points.
[0067] Optionally, the molar proportion of the benzophenone compound is 2.0 to 4.0 parts; the molar proportion of the fluorene compound is 1.0 to 1.2 parts; and the molar proportion of the p-aminophenylborate hydrochloride is 2.0 to 2.5 parts.
[0068] Optionally, in the aldol condensation reaction, the reaction temperature is 70 to 90° C., and the reaction time is 8 to 48 hours.
[0069] Optionally, in the aldol condensation reaction, the reaction temperature is selected from any value of 70°C, 75°C, 80°C, 85°C, 90°C or a range between any two of the above points.
[0070] Optionally, in the aldol condensation reaction, the reaction time is any value among 8 hours, 10 hours, 15 hours, 20 hours, 25 hours, 30 hours, 35 hours, 40 hours, 45 hours, 48 hours, or a range value between any two of the above points.
[0071] Optionally, in the aldol condensation reaction, the reaction temperature is 65° C. to 75° C., and the reaction time is 24 to 48 hours.
[0072] Optionally, in the aldol condensation reaction, the reaction temperature is selected from any value of 65° C., 70° C., 75° C., or a range between any two of the above points.
[0073] Optionally, in the aldol condensation reaction, the reaction time is any value among 24 hours, 25 hours, 30 hours, 35 hours, 40 hours, 45 hours, 48 hours, or a range between any two of the above points.
[0074] Optionally, the mixture I contains a solvent I, and the solvent I is selected from at least one of tetrahydrofuran, 1,4-dioxane, N-methylpyrrolidone, and dimethyl sulfoxide.
[0075] Optionally, in the Suzuki coupling reaction, the reaction temperature is 80 to 110° C., and the reaction time is 8 to 48 h.
[0076] Optionally, in the Suzuki coupling reaction, the reaction temperature is selected from any value of 80°C, 90°C, 100°C, 110°C or a range between any two of the above points.
[0077] Optionally, in the Suzuki coupling reaction, the reaction time is selected from any value of 8 hours, 10 hours, 15 hours, 20 hours, 25 hours, 30 hours, 35 hours, 40 hours, 45 hours, 48 hours, or a range between any two of the above points.
[0078] Optionally, in the Suzuki coupling reaction, the reaction temperature is 95° C. to 110° C., and the reaction time is 24 to 48 hours.
[0079] Optionally, in the Suzuki coupling reaction, the reaction temperature is selected from any value of 95° C., 100° C., 110° C., or a range between any two of the above points.
[0080] Optionally, in the Suzuki coupling reaction, the reaction time is selected from any value of 24 hours, 25 hours, 30 hours, 35 hours, 40 hours, 45 hours, 48 hours, or a range between any two of the above points.
[0081] Optionally, the mixture II contains a solvent II, and the solvent II is selected from at least one of tetrahydrofuran, 1,4-dioxane, and toluene.
[0082] Optionally, the solvent II is selected from at least one of tetrahydrofuran and water, 1,4-dioxane and water, and toluene and water.
[0083] Optionally, the solvent II is 1,4-dioxane.
[0084] According to the third aspect of the present application, a type of polyimide microcellular foam material is provided, wherein the polyimide microcellular foam material comprises the polyimide polymer described above.
[0085] Optionally, the specific surface area of the polyimide microporous foam material is 260 to 670 m 2 / g.
[0086] Optionally, the glass transition temperature of the polyimide microporous foam material is 260-400°C.
[0087] Optionally, the shrinkage rate of the polyimide microporous foam material is 7% to 15%.
[0088] Optionally, the thermal conductivity of the polyimide microporous foam material is 40 to 70 mW m -1 K -1 .
[0089] According to the fourth aspect of the present application, there is provided an application of the above-mentioned polyimide microporous foam material as a thermal insulation material or a separation material or an electromagnetic shielding material in aerospace, automobile manufacturing, electronics and electrical, gas separation, and sewage treatment.
[0090] The beneficial effects of this application include:
[0091] 1) The raw materials provided in this application are commercial products, the synthesis route is simple, the yield is high, and the synthesis method is universal. The diamine compound of the present invention has the structural characteristics of conjugation and non-coplanarity, and the skeleton has a certain rigidity and a certain torsion, so that the main chain structure of the polyimide has moderate rigidity; it has high temperature resistance, can reduce the shrinkage rate of microporous foam materials, and improve mechanical properties.
[0092] 2) The raw materials provided in this application are commercial products, cheap and easily available. The structure of the aromatic diamine is a new molecule, and the polyimide structure is a new polymer structure, which can be extended to the structural design of various polyimides.
[0093] 3) The polyimide microporous foam material provided in this application has high specific surface area, low shrinkage, high temperature resistance and excellent high temperature thermal insulation performance (specific surface area up to 670m 2 / g, the minimum shrinkage is 7.7%, the glass transition temperature can reach 376℃, and the thermal conductivity is as low as 41.5mW m at 150℃ -1 K -1 ), as a high-temperature thermal insulation material, it has very good application prospects in aerospace, space exploration and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0094] Figure 1 This is the H NMR spectrum of the intermediate 1 in Example 1 of the present application.
[0095] Figure 2 This is the H NMR spectrum of diamine I in Example 1 of the present application.
[0096] Figure 3 This is the NMR carbon spectrum of diamine I in Example 1 of the present application.
[0097] Figure 4 This is the mass spectrum of diamine I in Example 1 of the present application.
[0098] Figure 5 This is the infrared spectrum of polyimide I-1 in Example 1 of the present application.
[0099] Figure 6 This is the infrared spectrum of polyimide II-2 in Example 5 of the present application.
[0100] Figure 7 This is the H NMR spectrum of the intermediate 2 in Example 6 of the present application.
[0101] Figure 8 This is the H NMR spectrum of diamine II in Example 6 of the present application.
[0102] Fig. 9 This is the NMR carbon spectrum of diamine II in Example 6 of the present application.
[0103] Fig.10 This is the mass spectrum of diamine II in Example 6 of the present application.
[0104] Fig.11 This is the infrared spectrum of polyimide III-1 in Example 6 of the present application.
[0105] Fig.12This is the infrared spectrum of polyimide IV-2 in Example 7 of the present application. DETAILED DESCRIPTION
[0106] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0107] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0108] In the examples of the present application, the prepared aromatic diamine and polyimide microporous foams were characterized by the following instruments:
[0109] The obtained aromatic diamine was tested by Bruker AVANCE III HD 700MHz NMR spectrometer. 1 H NMR and 13 C NMR spectrum, the detection condition is to dissolve 30 mg of sample in deuterated dimethyl sulfoxide solvent for testing, the hydrogen spectrum is scanned 16 times, and the carbon spectrum is scanned 1024 times.
[0110] The HR-ESI-MS spectrum of the obtained aromatic diamine was tested using Agilent's Q-TOF 6540 liquid chromatography high-resolution time-of-flight mass spectrometer, and the detection condition was that 1 mg of the sample was dissolved in methanol for testing.
[0111] The infrared absorption spectrum of the obtained polyimide resin was tested by using Shimadzu's IRTracer-100 infrared spectrometer. The detection conditions were as follows: about 5 mg of the sample was dried in vacuum at 170 ° C for 12 hours, and then directly spread on the sample table for Fourier transform attenuated total reflection infrared spectroscopy (ATR-FTIR) test, scanning 16 times with a resolution of 4 cm -1 .
[0112] The differential scanning calorimetry results were collected by TA DSC25 instrument, the sample mass was about 5 mg, and the temperature change rate was 10 °C min -1 .
[0113] The thermal conductivity results were collected by a Hot Disk instrument from Thermometric AB. The sample diameter was 40 mm, the thickness was 15 mm, the test temperature was 150°C, the thermal conductivity was measured three times, and the average value was taken.
[0114] Example 1 Preparation of polyimide I-1
[0115] The synthetic route is as follows:
[0116]
[0117] 2,7-Dibromofluorene (0.97 g, 3.0 mmol, 1.0 equiv.) was added to a 100 mL three-necked flask. After nitrogen replacement three times, anhydrous tetrahydrofuran (THF, 20 mL) was added, the temperature was raised to 75 ° C, and refluxed and stirred for 4 hours. Benzophenone (1.31 g, 7.20 mmol, 2.4 equiv.) was added to the reaction system. After continuing the reflux reaction for 24 hours, the color of the solution gradually turned dark blue, and then the reaction was stopped. After cooling to room temperature, it was spin-dried and purified by column chromatography. The mobile phase was petroleum ether / dichloromethane-10 / 1 to obtain yellow powder intermediate 1 (1.20 g, yield 83.4%). Figure 1 is the hydrogen spectrum of intermediate 1, 1 H NMR (700MHz, CDCl3) δ7.51 (d, J = 8.1Hz, 2H), 7.48-7.44 (m, 6H), 7.37-7.34 (m, 6H), 6.68 (d, J = 1.1Hz, 2H).
[0118] The intermediate 1 (100 mg, 0.20 mmol, 1.0 equiv.), p-aminophenyl boron hydrochloride (66 mg, 0.48 mmol, 2.4 equiv.), tetrakis(triphenylphosphine)palladium (15 mg), 1,4-dioxane (8.4 mL), potassium carbonate solution (2.0 M, 1.8 mL), and 2 drops of methyltrioctylammonium chloride were placed in a 50 mL three-necked flask, and nitrogen was circulated once, and the temperature was raised to 95°C, and the mixture was stirred under reflux for 24 hours. The mixture was cooled to room temperature, dried, and purified by column chromatography, with the mobile phase being petroleum ether / ethyl acetate-1 / 3, to obtain a light yellow solid (84 mg, yield 84.4%). Figure 2 is the hydrogen spectrum of diamine I, Figure 3 is the carbon spectrum of diamine I, Figure 4 is the mass spectrum of diamine I. 1 H NMR(700MHz,DMSO-d6)δ7.77(d,J=7.7Hz,2H),7.57-7.54(m,4H),7.52-7.49(m,6H),7.45(d ,J=7.3,1.4Hz,2H),6.92(d,J=8.4Hz,4H),6.59(s,2H),6.51(d,J=8.4Hz,4H),5.18(s,4H). 13 C NMR(176MHz,DMSO-d6)δ148.64,145.64,143.09,139.00,138.99,138.05,133.97,129.70 ,128.96,128.50,127.93,127.12,125.58,122.24,120.21,114.53.HR-ESI-MScalcd.for C 38H 29 N2[M+H] + :513.2331; found:513.2294.
[0119] Diamine I (3.84 g, 7.50 mmol, 1.0 equiv.), 3,3',4,4'-biphenyltetracarboxylic dianhydride (2.28 g, 7.75 mmol, 1.03 equiv.), and N-methylpyrrolidone (48 mL) were mixed, stirred and reacted at 20°C for 12 hours, 1,3,5-tris(4-aminophenoxy)benzene (75 mg, 0.18 mmol) was added, and the reaction was continued for 30 minutes. Acetic anhydride (5.8 mL, 62.0 mmol) and pyridine (5.0 mL, 62.0 mmol) were added in sequence, stirred for 15 minutes, poured into a polytetrafluoroethylene liner, allowed to stand, aged for 1 day, and solvent replaced with acetone three times. Finally, it was dried with supercritical carbon dioxide at 10 MPa for 8 hours to obtain a yellow cylinder. Figure 5 is the infrared absorption spectrum of polyimide I-1. FT-IR (cm -1 ) 1777 (C=O asymmetric stretching), 1720 (C=O symmetric stretching), 1599, 1518 and 1463 (benzene ring), 1363 (-CN-asymmetric stretching), 736 (C=O bending). The glass transition temperature is 320.4°C.
[0120] Example 2 Preparation of polyimide I-2
[0121] The diamine I (3.84 g, 7.50 mmol, 1.0 equiv.) prepared in Example 1, 3,3',4,4'-biphenyltetracarboxylic dianhydride (2.28 g, 7.75 mmol, 1.03 equiv.), and dimethyl sulfoxide (48 mL) were mixed, stirred and reacted at 20°C for 12 hours, 1,3,5-tris(4-aminophenoxy)benzene (75 mg, 0.18 mmol) was added, and the reaction was continued for 30 minutes. Acetic anhydride (5.8 mL, 62.0 mmol) and pyridine (5.0 mL, 62.0 mmol) were added in sequence, stirred for 15 minutes, poured into a polytetrafluoro liner, allowed to stand, aged for 1 day, and solvent replaced with acetone 3 times. Finally, it was dried with supercritical carbon dioxide at 10 MPa for 8 hours to obtain a yellow cylinder.
[0122] Example 3 Preparation of polyimide I-3
[0123] The diamine I (3.84 g, 7.50 mmol, 1.0 equiv.) prepared in Example 1, 3,3',4,4'-biphenyltetracarboxylic dianhydride (2.28 g, 7.75 mmol, 1.03 equiv.), and N-methylpyrrolidone (48 mL) were mixed, stirred and reacted at 80° C. for 2 hours, 1,3,5-tris(4-aminophenoxy)benzene (75 mg, 0.18 mmol) was added, and the reaction was continued for 30 minutes. Acetic anhydride (5.8 mL, 62.0 mmol) and pyridine (5.0 mL, 62.0 mmol) were added in sequence, stirred for 15 minutes, poured into a polytetrafluoro liner, allowed to stand, aged for 1 day, and solvent replaced with acetone 3 times. Finally, it was dried with supercritical carbon dioxide at 10 MPa for 8 hours to obtain a yellow cylinder.
[0124] Example 4 Preparation of Polyimide II-1
[0125] The structural formula is as follows:
[0126]
[0127] The diamine I (1.92 g, 3.75 mmol, 0.5 equiv.) prepared in Example 1, 4,4'-diaminodiphenyl ether (0.75 g, 3.75 mmol, 0.5 equiv.), 3,3',4,4'-biphenyltetracarboxylic dianhydride (2.28 g, 7.75 mmol, 1.03 equiv.), and N-methylpyrrolidone (48 mL) were mixed, stirred and reacted at 20°C for 12 hours, 1,3,5-tris(4-aminophenoxy)benzene (75 mg, 0.18 mmol) was added, and the reaction was continued for 30 minutes. Acetic anhydride (5.8 mL, 62.0 mmol) and pyridine (5.0 mL, 62.0 mmol) were added in sequence. After stirring for 15 minutes, the mixture was poured into a polytetrafluoro liner, allowed to stand, aged for 1 day, and solvent replaced with acetone 3 times. Finally, the mixture was dried with supercritical carbon dioxide at 10 MPa for 8 hours to obtain a yellow cylinder.
[0128] Example 5 Preparation of Polyimide II-2
[0129] The diamine I (0.96 g, 1.87 mmol, 0.25 equiv.) prepared in Example 1, 4,4'-diaminodiphenyl ether (1.13 g, 5.63 mmol, 0.75 equiv.), 3,3',4,4'-biphenyltetracarboxylic dianhydride (2.28 g, 7.75 mmol, 1.03 equiv.), and N-methylpyrrolidone (48 mL) were mixed, stirred and reacted at 20°C for 12 hours, 1,3,5-tris(4-aminophenoxy)benzene (75 mg, 0.18 mmol) was added, and the reaction was continued for 30 minutes. Acetic anhydride (5.8 mL, 62.0 mmol) and pyridine (5.0 mL, 62.0 mmol) were added in sequence. After stirring for 15 minutes, the mixture was poured into a polytetrafluoro liner, allowed to stand, aged for 1 day, and solvent replaced with acetone three times. Finally, the mixture was dried with supercritical carbon dioxide at 10 MPa for 8 hours to obtain a yellow cylinder. Figure 6 is the infrared absorption spectrum of polyimide II-2. FT-IR (cm -1 ) 1780 (C=O asymmetric stretching), 1720 (C=O symmetric stretching), 1600 and 1518 (benzene ring), 1375 (-CN-asymmetric stretching), 737 (C=O bending). The glass transition temperature is 263.5°C.
[0130] Example 6 Preparation of Polyimide III-1
[0131] The synthetic route is as follows:
[0132]
[0133] Fluorene (1.0 g, 6.0 mmol, 1.0 equiv.) was added to a 100 mL three-necked flask. After nitrogen replacement three times, anhydrous tetrahydrofuran (THF, 50 mL) was added, the temperature was raised to 75 ° C, and refluxed and stirred for 4 hours, and 4,4'-dibromobenzophenone (4.89 g, 14.4 mmol, 2.4 equiv.) was added to the reaction system. After continuing the reflux reaction for 24 hours, the color of the solution gradually turned dark blue, and then the reaction was stopped. After cooling to room temperature, it was spin-dried and purified by column chromatography. The mobile phase was petroleum ether / dichloromethane-10 / 1 to obtain yellow powder intermediate 2 (2.40 g, yield 82.3%). Figure 7 is the hydrogen spectrum of intermediate 2, 1 H NMR(700MHz, CDCl3) δ7.69(d,J=7.7Hz,2H),7.55(d,J=8.4Hz,4H),7.27(t,J=7 .7Hz,2H),7.23(d,J=8.4Hz,4H),6.97(t,J=7.7Hz,2H),6.71(d,J=8.4Hz,2H).
[0134] The intermediate 2 (100 mg, 0.20 mmol, 1.0 equiv.), p-aminophenyl boron hydrochloride (66 mg, 0.48 mmol, 2.4 equiv.), tetrakis(triphenylphosphine)palladium (15 mg), 1,4-dioxane (8.4 mL), potassium carbonate solution (2.0 M, 1.8 mL), and 2 drops of methyltrioctylammonium chloride were placed in a 50 mL three-necked flask, and nitrogen was circulated once, and the temperature was raised to 95°C, and the mixture was stirred under reflux for 24 hours. The mixture was cooled to room temperature, dried, and purified by column chromatography, with the mobile phase being petroleum ether / ethyl acetate-1 / 3, to obtain a light yellow solid (84 mg, yield 84.4%). Figure 8 is the hydrogen spectrum of diamine II, Fig. 9 is the carbon spectrum of diamine II, Fig.10 This is the mass spectrum of diamine II. 1 HNMR(700MHz,DMSO-d6)δ7.86(d,J=7.7Hz,2H),7.67(d,J=8.4Hz,4H),7.48(d,J=8.4Hz,4H),7.35(d,J=8.4Hz ,4H),7.27(t,J=7.7Hz,2H),6.99(t,J=7.7Hz,2H),6.74(d,J=8.4Hz,2H),6.67(d,J=8.4Hz,4H),5.32(s,4H). 13 C NMR(176MHz,DMSO-d6)δ149.27,146.38,141.00,140.20,140.16,138.60,133.20,1 30.41,128.14,127.69,126.99,126.77,125.91,124.71,120.17,114.74.HR-ESI-MS calcd.for C 38 H 29 N2[M+H] + :513.2331; found:513.2355.
[0135] Diamine II (3.84 g, 7.50 mmol, 1.0 equiv.), 3,3',4,4'-biphenyltetracarboxylic dianhydride (2.28 g, 7.75 mmol, 1.03 equiv.), and N-methylpyrrolidone (48 mL) were mixed, stirred and reacted at 20°C for 12 hours, 1,3,5-tris(4-aminophenoxy)benzene (75 mg, 0.18 mmol) was added, and the reaction was continued for 30 minutes. Acetic anhydride (5.8 mL, 62.0 mmol) and pyridine (5.0 mL, 62.0 mmol) were added in sequence, stirred for 15 minutes, poured into a polytetrafluoro liner, allowed to stand, aged for 1 day, and solvent replaced with acetone three times. Finally, it was dried with supercritical carbon dioxide at 10 MPa for 8 hours to obtain a yellow cylinder. Fig.11 is the infrared absorption spectrum of polyimide III-1. FT-IR (cm -1 )1777 (C=O asymmetric stretching), 1722 (C=O symmetric stretching), 1612, 1493 and 1442 (benzene ring), 1367 (-CN-asymmetric stretching), 734 (C=O bending).
[0136] Example 7 Preparation of Polyimide III-2
[0137] The diamine II prepared in Example 6 (3.84 g, 7.50 mmol, 1.0 equiv.), 3,3',4,4'-biphenyltetracarboxylic dianhydride (2.28 g, 7.75 mmol, 1.03 equiv.), and dimethyl sulfoxide (48 mL) were mixed, stirred and reacted at 20° C. for 12 hours, 1,3,5-tris(4-aminophenoxy)benzene (75 mg, 0.18 mmol) was added, and the reaction was continued for 30 minutes. Acetic anhydride (5.8 mL, 62.0 mmol) and pyridine (5.0 mL, 62.0 mmol) were added in sequence, stirred for 15 minutes, poured into a polytetrafluoro liner, allowed to stand, aged for 1 day, and solvent replaced with acetone 3 times. Finally, it was dried with supercritical carbon dioxide at 10 MPa for 8 hours to obtain a yellow cylinder.
[0138] Example 8 Preparation of Polyimide III-3
[0139] The diamine II prepared in Example 6 (3.84 g, 7.50 mmol, 1.0 equiv.), 3,3',4,4'-biphenyltetracarboxylic dianhydride (2.28 g, 7.75 mmol, 1.03 equiv.), and N-methylpyrrolidone (48 mL) were mixed, stirred and reacted at 80° C. for 2 hours, 1,3,5-tris(4-aminophenoxy)benzene (75 mg, 0.18 mmol) was added, and the reaction was continued for 30 minutes. Acetic anhydride (5.8 mL, 62.0 mmol) and pyridine (5.0 mL, 62.0 mmol) were added in sequence. After stirring for 15 minutes, the mixture was poured into a polytetrafluoro liner, allowed to stand, aged for 1 day, and solvent replaced with acetone 3 times. Finally, the mixture was dried with supercritical carbon dioxide at 10 MPa for 8 hours to obtain a yellow cylinder.
[0140] Example 9 Preparation of Polyimide IV-1
[0141] The structural formula is as follows:
[0142]
[0143] The diamine II prepared in Example 6 (1.92 g, 3.75 mmol, 0.5 equiv.), 4,4'-diaminodiphenyl ether (0.75 g, 3.75 mmol, 0.5 equiv.), 3,3',4,4'-biphenyltetracarboxylic dianhydride (2.28 g, 7.75 mmol, 1.03 equiv.), and N-methylpyrrolidone (48 mL) were mixed, stirred and reacted at 20°C for 12 hours, 1,3,5-tris(4-aminophenoxy)benzene (75 mg, 0.18 mmol) was added, and the reaction was continued for 30 minutes. Acetic anhydride (5.8 mL, 62.0 mmol) and pyridine (5.0 mL, 62.0 mmol) were added in sequence. After stirring for 15 minutes, the mixture was poured into a polytetrafluoro liner, allowed to stand, aged for 1 day, and solvent replaced with acetone 3 times. Finally, the mixture was dried with supercritical carbon dioxide at 10 MPa for 8 hours to obtain a yellow cylinder.
[0144] Example 10 Preparation of aromatic diamine IV-2
[0145] The diamine II prepared in Example 6 (1.92 g, 3.75 mmol, 0.5 equiv.), 4,4'-diaminodiphenyl ether (0.75 g, 3.75 mmol, 0.5 equiv.), 3,3',4,4'-biphenyltetracarboxylic dianhydride (2.28 g, 7.75 mmol, 1.03 equiv.), and N-methylpyrrolidone (48 mL) were mixed, stirred and reacted at 20°C for 12 hours, 1,3,5-tris(4-aminophenoxy)benzene (75 mg, 0.18 mmol) was added, and the reaction was continued for 30 minutes. Acetic anhydride (5.8 mL, 62.0 mmol) and pyridine (5.0 mL, 62.0 mmol) were added in sequence. After stirring for 15 minutes, the mixture was poured into a polytetrafluoro liner, allowed to stand, aged for 1 day, and solvent replaced with acetone 3 times. Finally, the mixture was dried with supercritical carbon dioxide at 10 MPa for 8 hours to obtain a yellow cylinder. Fig.12 is the infrared absorption spectrum of polyimide IV-2. FT-IR (cm -1 )1776 (C=O asymmetric stretching), 1716 (C=O symmetric stretching), 1612 and 1499 (benzene ring), 1370 (-CN-asymmetric stretching), 738 (C=O bending).
[0146] Table 1. Physical and chemical properties of polyimide microporous foam materials
[0147]
[0148]
[0149] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A polyimide polymer, characterized in that: The polyimide polymer has a structure shown in Formula I: Wherein, n is 10 to 100; In Formula I, R4 is selected from one of the compounds represented by Formula I-1 and Formula I-2; R1 is selected from one of the structures shown in A-1 to A-10; R2 is selected from one of the structures shown in B-1 to B-13; R3 is selected from one of the structures shown in Formula I-3, Formula I-4, Formula I-5, and Formula I-6; 2. The method for preparing the polyimide polymer according to claim 1, characterized in that: The following steps are involved: Reacting a mixture containing a compound represented by Formula II, a dianhydride compound, a compound represented by Formula III, and a solvent to obtain a polyimide polymer represented by Formula I; Wherein, the compound represented by formula II is selected from one of the structures represented by formula II-1 and formula II-2; the compound represented by formula III is selected from one of the structures represented by formula III-1, formula III-2, formula III-3, and formula III-4; 3. The preparation method according to claim 2, characterized in that: The dianhydride compound is selected from at least one of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 1,4-bis(trifluoromethyl)-2,3,5,6-pyromellitic dianhydride, 4,4'-oxydiphthalic anhydride, 4,4'-thiodiphthalic anhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 4,4'-(hexafluoroisopropylene)diphthalic anhydride, 3,3,4,4-diphenylsulfonetetracarboxylic dianhydride, and 4,4'-(4,4'-isopropyldiphenoxy)bis(phthalic anhydride).
4. The preparation method according to claim 2, characterized in that: The molar ratio of the compound represented by formula II, the dianhydride compound and the compound represented by formula III is: 0.90-0.99: 1.01-1.10: 0.01-0.
05.
5. The preparation method according to claim 2, characterized in that: The molar volume ratio of the compound represented by formula II to the solvent is 3.75-7.50 mmol: 20-50 mL.
6. The preparation method according to claim 2, characterized in that: The solvent is selected from at least one of N,N-dimethylformamide, N,N-diethylacetamide, dimethyl sulfoxide, tetrahydrofuran, and 1,4-dioxane.
7. The preparation method according to claim 2, characterized in that: The reaction temperature is 10°C to 180°C, and the reaction time is 2 to 24 hours; Preferably, the reaction temperature is 20°C to 30°C, and the reaction time is 8 to 12 hours.
8. A type of polyimide microporous foam material, characterized in that: The polyimide microcellular foam material comprises the polyimide polymer according to claim 1.
9. The polyimide microporous foam material according to claim 8, characterized in that: The specific surface area of the polyimide microporous foam material is 260 to 670 m 2 / g; Preferably, the glass transition temperature of the polyimide microporous foam material is 260 to 400°C; Preferably, the shrinkage rate of the polyimide microporous foam material is 7% to 15%; Preferably, the thermal conductivity of the polyimide microporous foam material is 40 to 70 mW m -1 K -1 .
10. Use of the polyimide microporous foam material according to claim 8 or 9 as a thermal insulation material or a separation material or an electromagnetic shielding material in aerospace, automobile manufacturing, electronics and electrical, gas separation, and sewage treatment.
Citation Information
Patent Citations
Polymer, preparation method thereof and application of polymer as aerogel
CN116262828A
Polymer, preparation method thereof and application of polymer as foam material
CN116262829A
Soluble polyimide and its production
JP2000053767A
Flexible isopropylidene and tetramethyl-containing fluoropolyamide and fluoropolyimide and preparation method thereof
US20050101756A1
Cited By
Aromatic diamine compound as well as preparation method and application thereof
CN117486733A